Effects of topical treatment of second-degree burn wounds with Lactobacillus acidophilus on the wound healing process in male rats - Amir Abbas Barzegari; Masood Hashemzaei; Raheleh Majdani; Ali-Reza Alihemmati (Mazandaran University of Medical Sciences, 2017)
Despite preventive measures, incidence of burns is still one of the important medical problems. Nowadays, it has been suggested that some strains of probiotic bacteria have beneficial effects in treatment of skin injures like skin wounds. The aim of the present study was to evaluate the effects of Lactobacillus acidophilus on second-degree burn wounds in rats. Second-degree burn wounds were induced on the back of the 60 Wistar rats by contacting of a heated aluminum bar. After that, the rats randomly assigned to negative control (received no treatment), vehicle control (received Eucerin, daily) and experimental (received daily, an ointment of bacteria in Eucerin) groups. Macroscopic assessment of wound healing was conducted by calculating the percent of wound healing in days 3, 7 and 14 post-burn. Moreover, wound samples were harvested for microscopic evaluation of wound area. The results showed that in the experimental groups, the percent of wound healing, in the 3th and 7th days of experiments was significantly higher than control group. Moreover, in addition to prevention of burn infection, the bacteria had beneficial effects on different aspects of wound healing processes like reducing the inflammatory response and accelerating the granulation tissue formation and re-epithelialization. Overall, the present study showed that the treatment of burn wounds with L. acidophilus might accelerate the healing processes of second-degree burn wounds.